Regional payments mechanisms: the case of Puerto Rico - Ingram, James C. (Chapel Hill : University of North Carolina Press, 1962)
This book is a study of interregional economic adjustment within the United States 'common Market' area, of which Puerto Rico offers important advantage because it is closely integrated with the United States economy. The study examine how adjustments of prices and incomes react to changes in trade or capital flows.
Includes index
Includes bibliography.
usc 10/04/18
Loans
Keywords: Balance of payments